Nuts about trees? Smallholders' diverse agroforestry systems and their relationship to groundnut yields in the Senegalese Groundnut Basin - Luisa Müting; Petros Suzgo Kayovo Mkandawire; Oliver Mußhoff (Georg-August University of Göttingen, RTG 2654 Sustainable Food Systems, 2024)
In the Sahel region, agroforestry potentially increases crop yields, alongside restoring and retaining soils. Nonetheless, little is known about how diverse agroforestry systems perform across actual agricultural systems of smallholders in the region. We therefore investigate how smallholders' different agroforestry systems in the Senegalese Groundnut Basin relate to groundnut yields. We distinguish agroforestry systems by (a) tree quantity per hectare, (b) tree species diversity and (c) quantities per hectare of the most prevalent tree species in our data. Using data of 492 groundnut farmers, collected in the Groundnut Basin from December 2022 to January 2023, we estimate log-linearized Cobb-Douglas-production functions through ordinary least squares regression. 53 tree species were reported by 93.8% of smallholders. We identify Faidherbia albida, Cordyla pinnata, Adansonia digitata, Anogeissus leiocarpa, and Ziziphus mauritiana as most prevalent species. Our results indicate that groundnut yields initially increase with tree quantity and species diversity. However, at too many trees per hectare the competition between trees and crops for space and nutrients seems to outweigh the benefits. Faidherbia albida trees are beneficial for groundnut yield outcomes only at a higher number of these trees. For the species Cordyla pinnata and Anogeissus leiocarpa, additional trees initially lead to increases in groundnut yields. The tree species Ziziphus mauritiana and Adansonia digitata appear to have no association with groundnut yields. We find a remaining potential of increasing tree cover or tree species diversity and introducing or expanding certain tree species in established agroforestry systems to enhance synergies between land restoration and groundnut productivity.
Keywords: Q12; Q19; Q23; 330; Agroforestry; Tree quantity; Tree species diversity; Prevalent tree species; Groundnut yields; Smallholders; Senegalese Groundnut Basin